SOSIALISASI ASPEK MANAJEMEN DAN EKONOMI DI PANTAI LHOK BUBON KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Zuriat Zuriat (Universitas Teuku Umar, 2019)
Coastal area is fishermen’s home area and landed catch fish as an activity of economic life. Lhok Bubon Village is beach subdistrict of fishermen and tourism place for West Aceh community. The coastal area is front of the open oceans have beautiful scene with shallow beach and low wave. This village have a lot of local tourist. Thus, it is necessary to elevate with bussiness such as restaurant and other services. The empowering community was undertaken for giving awareness to local community from management aspect and productive economic activity where the need to tourism are secondary need. With adequate facilities and keep cleanliness of the beach. It have opportunity to be tourism place that priority for local community as marine tourim site. Economical empowerment to be one of material that conveyed to increasing the motivation for women in order to utilize the potency of coastal resources as transport of family economic in management aspect such as plannning, organizing, actuacting of tourism services as well as surveilance aspect and islamic tourism site for West Aceh community especially outside West Aceh.